SAT0025 MIR 106A, MIR 19A-B, MIR 20A and MIR21A regulate vγ9vδ2 functions participating in the inflammatory responses occurring in rheumatoid arthritis. (15th June 2017) - Guggino, G; Ciccia, F; Orlando, V; SAieva, L; Ruscitti, P; Cipriani, P; Chalcarz, I; Alessandro, R; Giacomelli, R; Dieli, F; Caccamo, N; Triolo, G
Abstract : Background: miRNAs are non-coding RNAs which have significant roles in regulating gene expression. The miR17-92 cluster appears to be a key factor in the inflammatory pathways activated during RA. Objectives: In this study we aimed to evaluate miR17–92 expression and functions in γδ T cell subsets in RA patients, γδ T cells, in fact produce proinflammatory cytokines such as IFN-g, IL-6 and IL-8 that may contribute to the inflammatory responses in RA. Methods: Heparinized peripheral blood from 10 early RA untreated patients and 10 healthy donors was obtained for this study. Polyclonal Vγ9Vδ2 T cell lines were generated first by magnetic isolation followed by sorting (FACSAria) and further analysed by flow cytometry to define their phenotype and their pattern of cytokine production. Expression analysis of miRNA17–92 cluster was performerd by RT-PCR and after identification of relevant miRNA involved in RA, mRNA expression of miRNA target genes was studied. Results: A remarkable change in the distribution of Vγ9Vδ2 T cell functional subsets with an expansion of effector subsets and a reduction of naïve cells, was observed in the peripheral blood of RA patients, as compared to healthy donors, which were accompanied by modifications in proinflammatory cytokine expression. Particularly, TEM (effector memory) and TEMRA (effector memory terminally differentiated) cells resulted the major souce of IL-6 and IL-8. A significant correlation between miRNA expression and levels of IL-6 and IL-8 was found. The comparative analysis of miRNA expression among Vγ9Vδ2 T cell subsets, between RA patients and healthy controls showed a downregulation of miR106a-5p and miR20a-5p and an upregulation of miR 21a-5p among Vγ9Vδ2 TEM cells; a downregulation of miR19–3p among Vγ9Vδ2 TEM and TcM (central memory) cells was also found. This miRNA expression regulated IL-8 and IL-6 gene transcription contributing to the survival of the pro-inflammatory pool reducing the expression of the PDCD4 gene. Conclusions: Our results provide evidence of a role of miR106a, miR19–3p, 20a and 21a in the regulation of Vγ9Vδ2 T cells function in RA patients and suggest the possibility that the miR17–92 family and γδ T cells participate to the pathogenesis of RA. Disclosure of Interest: None declared